Age-dependent dysfunction of the cerebrovascular system in the zebrafish telencephalon - Takamasa Mizoguchi; Mayu Okita; Yuina Minami; Misa Fukunaga; Ayumi Maki; Motoyuki Itoh (Experimental Gerontology, 2023)
The brain is an essential organ that controls various biological activities via the nervous system. The cerebral blood vessels supply oxygen and nutrients to neuronal cells and carry away waste products, which is essential in maintaining brain functions. Aging affects cerebral vascular function and decreases brain function. However, the physiological process of age-dependent cerebral vascular dysfunction is not fully understood. In this study, we examined aging effects on cerebral vascular patterning, vascular function, and learning ability in adult zebrafish. We found that the tortuosity of the blood vessels was increased, and the blood flow rate was reduced with aging in the zebrafish dorsal telencephalon. Moreover, we found cerebral blood flow positively correlated with learning ability in middle-old-aged zebrafish, as in aged humans. In addition, we also found that the elastin fiber decreased in the middle-old-aged fish brain vessel, suggesting a possible molecular mechanism underlying vessel dysfunction. Therefore, adult zebrafish may serve as a useful model for studying the aging-dependent decline in vascular function and human diseases such as vascular dementia.